2015
DOI: 10.1039/c5nj01875g
|View full text |Cite
|
Sign up to set email alerts
|

Bis(pyridylpyrazolate)platinum(ii): a mechanochromic complex useful as a dopant for colour-tunable polymer OLEDs

Abstract: Electronic Supplementary Information (ESI) available: Schematic representation of pplymer-OLED devices and normalised EL spectra of these devices as a function of bias current. SeeThe photoluminescent and mechanochromic behaviour of bis(3-(3,5-bis(dodecyloxy)phenyl)-(5-pyridin-2yl)pyrazolate)platinum(II) complex PT12, selected from a series of Pt(II) compounds having N,N'-pyridylpyrazolate ligands, has been investigated. The electroluminescent properties of polymer OLEDs based on PT12-doped polyfluorene (PFO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…18 , 23 In addition, little attention has been paid to the carrier transport properties of chromic compounds. 4 , 11 , 15 , 24 – 26 …”
Section: Introductionmentioning
confidence: 99%
“…18 , 23 In addition, little attention has been paid to the carrier transport properties of chromic compounds. 4 , 11 , 15 , 24 – 26 …”
Section: Introductionmentioning
confidence: 99%
“…There are many advantages that make conjugated polymers attractive as emissive materials in organic light-emitting diode (OLED) devices. Examples of these advantages are low operating voltage, low cost of fabrication, ease of processing and manufacturing, flexibility, capability to build devices with large-area and good solubility in common organic solvents and photothermal stability [1,2,3,4]. OLEDs with various colors can be achieved by several techniques, such as: (i) building bilayers in a tandem diode structure [5,6]; (ii) using a single polymer with multiple functional groups [7,8]; (iii) blending of conjugated polymers [9,10]; (iv) mixing polymers with nanostructured materials [11,12], quantum dots [13,14] and small phosphorescent [15,16] or fluorescent [8,17] molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, these Pt(II) metallomesogens also exhibit electroluminescence properties, and one of them (n = 12) was selected as a prototype to develop polymer OLEDs. 190 The idea, described by the same authors, was taking advantage of the chromic response of the Pt(II) complex and the emission properties of PFO and fluorenone to fabricate workable whiteemitting LEDs (W-OLEDs). Results have shown that in those devices fabricated by doping the PFO matrix with just only 3% of the Pt(II) complex, Pt•••Pt interactions are induced and, concomitantly, the greenish emission of Pt(II) monomers turned on a bright-orange one.…”
Section: Square-planar Pt(ii) Complexesmentioning
confidence: 99%
“…CIE coordinates of the polymer OLED fabricated with the Pt­(II) metallomesogen 93 ( n = 12) . Reproduced with permission from ref .…”
Section: Phosphorescent Pt(ii) and Ir(iii) Metallomesogensmentioning
confidence: 99%
See 1 more Smart Citation